Variabilidade espacial da compactação superficial e subsuperficial de uma topossequência sob pastagem. - Ribeiro, Thiago de Souza (2012)
Soils have naturally variability in their intrinsic aspects, these variations are very importance in survey studies, physical characterization and experimental design of agricultural areas. Thus, this study aimed to assess the degree of spatial variability of soil compaction on a grassland toposequence using an automated penetrometer. The study was conducted in a slope with an area of approximately 2.0 ha, located in the watershed Vaca Brava, Areia-PB, in Red Yellow Argisol.. For the geostatistical analysis of the penetrometer readings (PR), the soil was sampled in a grid with regular mesh at intervals of 5.0, 10.0 and 20.0 m in the same line between the sampling points, totaling 108 points to a depth of 30 cm. Results werestratified in layers of 0-10 cm, 11-20 cm and 21-30 cm. The spatial variability, was analyzed using geostatisticas, and kriging interpolation of the data for map construction. The PR showed spatial dependence for all positions and depths that were related to variations in relief positions. The 0-10 and 21-30 cm layers were adjusted to a spherical model with indications of moderate spatial dependence. The 11-20 cm layer was adjusted to the exponential model with a weak degree of spatial dependence. The higher ranges for PR were observed for the 0-10 and 21-30 cm layers, as in the layer of 11-20 cm gave the lowest value for the range showing greater variability and lower spatial continuity. The highest values for the PR soil were found in the shoulder (upper) segment of the slope at all depths, identifying a compacted zonein the superficial layer. There was an increase in the penetration resistance with depth in all positions of the slope in the subsurface layer between 0-10 cm and 11-20 cm.. In the 21-30 cm layer there was greater continuity of lower penetrometer readings mainly in the mid-slope and lower slope segments.